Membangun Website Kecamatan Dempo Selatan - risnaini ris (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
This study aims to design and build a website in the District of South Dempo that makes it easier for the general public and government agencies, especially the people of the District of South Dempo, to find information about notifications quickly, and can be accessed anytime and anywhere. The problem at the Dempo Sub-District Head Office is the difficulty of delivering information to the wider community and requiring the community to come directly to the Office of the South Dempo Sub-District Head. In this study the data collection method carried out was by observation, interview and literature study. System development methods use the waterfall method with stages of analysis, design, coding and testing. This system was developed using Adobe Dreamweaver CS3, Php, MySql, and Xampp applications. The results of the research are in the form of Web-Based Design of Pagar Alam Selatan District Website. System testing uses usability testing with an average value of 4.63, which means that the user states that this website can facilitate the Dempo Selatan District to convey information and also facilitate parties who want to get information quickly and can be accessed anytime and anywhere.